2020
DOI: 10.22323/2.19020204
|View full text |Cite
|
Sign up to set email alerts
|

Chanting to the choir: the dialogical failure of antithetical climate change blogs

Abstract: Blogs provide potential for publics to engage more deliberatively through dialogue in controversial science than one-way dissemination methods. This study investigated who was commenting on two antithetical climate change blogsites; how they were commenting; and the quality of their dialogue. Most research into science blogs has focused on bloggers rather than commenters. This study found that both blogsites were dominated by a small number of commenters who used contractive dialogue to promote their own views… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
4
0
1
Order By: Relevance
“…17 The Media Bias/Fact Check website rates DeSmog UK as "left biased based on its political stance regarding climate change", and presents it as "an excellent source for researching who is funding climate science denial" (https://mediabiasfactcheck.com/ desmog/). 18 Contractive dialogic structures have also been the focus of recent studies of reader comments posted in response to climate change blogs (Metcalfe, 2020). 19 The Metafacet tool (Sheehan and Luz, 2019;Luz and Sheehan, 2020) draws on concordances generated while conducting searches for lexical items such as 'bias' to generate visualizations that display the number of concordance lines associated with a particular facet of the metadata-in this case, specific blogs.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…17 The Media Bias/Fact Check website rates DeSmog UK as "left biased based on its political stance regarding climate change", and presents it as "an excellent source for researching who is funding climate science denial" (https://mediabiasfactcheck.com/ desmog/). 18 Contractive dialogic structures have also been the focus of recent studies of reader comments posted in response to climate change blogs (Metcalfe, 2020). 19 The Metafacet tool (Sheehan and Luz, 2019;Luz and Sheehan, 2020) draws on concordances generated while conducting searches for lexical items such as 'bias' to generate visualizations that display the number of concordance lines associated with a particular facet of the metadata-in this case, specific blogs.…”
Section: Articlementioning
confidence: 99%
“…a subset of the Genealogies of Knowledge Internet corpus referred to in this article as the Climate Science Blogger Corpus (CSBC). 3 In focusing on blogs, this paper also intersects with a fast developing body of scholarship within the wider field of science communication that investigates climate change debates held in online public arenas between scientific expert bloggers and their readers (Lörcher and Taddicken, 2017); and explores how commenters on controversial science blogs are consolidating increasingly polarized publics, rather than fostering a more deliberative engagement across mutually opposing constituencies (Metcalfe, 2020). In order to facilitate the study of the multivoiced debate on climate science, CSBC features material written from a range of competing perspectives, not confined to the two poles between which the entrenched dialectic between 'alarmists' and 'deniers' is played out (Howarth and Sharman, 2015).…”
mentioning
confidence: 99%
“…L'auteure montre que sur les blogs, les internautes s'intéressent moins à l'argumentation de leurs adversaires qu'à leur qualité. La focalisation sur le commentateur prend le dessus sur le contenu de la conversation (Metcalfe, 2020).…”
Section: Discussionunclassified
“…The audiences of the websites and hence the potential reach of these efforts have not been subject of this study. Research indicates that climate science communication efforts risk "chanting to the choir" [Metcalfe, 2020]. Further research should examine whether the same applies to activist movements acting as alternative science communicators or whether they succeed in reaching alternative audiences, too.…”
Section: Discussionmentioning
confidence: 99%
“…However, what users do with this potential for heterogeneity across form, source, and content, can differ vastly between online spaces. An analysis of comments on two English-speaking climate blogs showed that commentators only engaged within like-minded groups and focused on one-way communication [Metcalfe, 2020]. In an analysis of German climate change discussions online, generalization across different spaces proved difficult, revealing the presence of various "online public arenas" with overlapping but distinctly different interests and commenting practices [Lörcher and Taddicken, 2017].…”
Section: Social Movements Onlinementioning
confidence: 99%